Human-Based Advanced in vitro Approaches to Investigate Lung Fibrosis and Pulmonary Effects of COVID-19 - Kiener, Mirjam; Roldan, Nuria; Machahua, Carlos; Sengupta, Arunima; Geiser, Thomas; Guenat, Olivier Thierry; Funke-Chambour, Manuela; Hobi, Nina; Kruithof-de Julio, Marianna (Frontiers in Medicine, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has caused considerable socio-economic burden, which fueled the development of treatment strategies and vaccines at an unprecedented speed. However, our knowledge on disease recovery is sparse and concerns about long-term pulmonary impairments are increasing. Causing a broad spectrum of symptoms, COVID-19 can manifest as acute respiratory distress syndrome (ARDS) in the most severely affected patients. Notably, pulmonary infection with Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2), the causing agent of COVID-19, induces diffuse alveolar damage (DAD) followed by fibrotic remodeling and persistent reduced oxygenation in some patients. It is currently not known whether tissue scaring fully resolves or progresses to interstitial pulmonary fibrosis. The most aggressive form of pulmonary fibrosis is idiopathic pulmonary fibrosis (IPF). IPF is a fatal disease that progressively destroys alveolar architecture by uncontrolled fibroblast proliferation and the deposition of collagen and extracellular matrix (ECM) proteins. It is assumed that micro-injuries to the alveolar epithelium may be induced by inhalation of micro-particles, pathophysiological mechanical stress or viral infections, which can result in abnormal wound healing response. However, the exact underlying causes and molecular mechanisms of lung fibrosis are poorly understood due to the limited availability of clinically relevant models. Recently, the emergence of SARS-CoV-2 with the urgent need to investigate its pathogenesis and address drug options, has led to the broad application of in vivo and in vitro models to study lung diseases. In particular, advanced in vitro models including precision-cut lung slices (PCLS), lung organoids, 3D in vitro tissues and lung-on-chip (LOC) models have been successfully employed for drug screens. In order to gain a deeper understanding of SARS-CoV-2 infection and ultimately alveolar tissue regeneration, it will be crucial to optimize the available models for SARS-CoV-2 infection in multicellular systems that recapitulate tissue regeneration and fibrotic remodeling. Current evidence for SARS-CoV-2 mediated pulmonary fibrosis and a selection of classical and novel lung models will be discussed in this review.